UNDERSTANDING ACUTE MALNUTRITION: A GLOBAL LITERATURE REVIEW ON RISK PROFILES IN UNDER-FIVE CHILDREN - Anwar Lubis (Yayasan Nuraini Ibrahim Mandiri, 2025)
Acute malnutrition in children under five remains a complex and multidimensional global public health issue. This study aims to identify and analyze the key risk factors of acute malnutrition based on a review of 10 primary research articles from various developing countries published between 2016 and 2024. A narrative literature review method was used, guided by the UNICEF conceptual framework that categorizes the causes of malnutrition into immediate, underlying, and basic levels. The findings reveal that inadequate feeding practices, recurrent infectious diseases, low maternal education, household poverty, food insecurity, and poor sanitation are the most consistently associated factors with wasting and SAM. Thematic analysis also highlights the interplay between socioeconomic status and poor caregiving as major determinants. The study concludes that nutrition interventions must be integrated with maternal education, improved sanitation, and household economic empowerment. These findings have important implications for evidence-based policy formulation at national and international levels.